INVESTIGATING THE RELATIONSHIP BETWEEN EXCESSIVE GADGET USE AND LEARNING CHALLENGES IN STUDENTS: A DIAGNOSTIC REVIEW - Agusthina Siahaya; Mohamad Sarip; Adi Mursalin; Mercy Florence Halamury; Ilona Flora Salhuteru (CV. ADIBA AISHA AMIRA, 2023)
The increasing prevalence of excessive gadget use among students in educational settings has become a prominent concern. This article presents a diagnostic review that explores the correlation between excessive gadget use and difficulties encountered by students in acquiring fundamental academic skills. The study compiles data from various research conducted in recent years, revealing that excessive gadget use can impair students' learning abilities in school. Firstly, extensive gadget usage tends to distract students, impeding their ability to concentrate on academic tasks such as class participation and homework completion. Furthermore, excessive gadget use can lead to eye fatigue and disrupt sleep quality, negatively affecting concentration and memory. Secondly, an over-reliance on gadgets reduces the time allocated for physical activities and social interactions, which play a vital role in children's development. Insufficient physical activity can adversely affect students' physical and cognitive health, while a lack of social interaction hinders their communication and collaborative skills with peers. The study emphasizes the urgent need for increased awareness and collective efforts from educators, parents, and the community to address excessive gadget use among students, fostering a healthy and conducive learning environment. Promoting responsible gadget usage is crucial for enhancing the overall quality of education in schools.